Adsorption of Pyridine by Acid Treated Spent Bleaching Earth - Mahramanlioglu, Mehmet; Ozgen, Ozge; Cinarli, Adem; Kizilcikli, Irfan (Asian Journal of Chemistry, 2010)
The adsorption of pyridine on acid treated spent bleaching earth was studied as a function of time, pH and initial concentration. Lagergren first order rate equation was used to describe the adsorption rate of pyridine and adsorption rate constants were calculated. Rate constants of intraparticle diffusion were also calculated. Adsorption isotherms were modelled by the Langmuir equation and the constants of this isotherm were calculated. The dependence of the adsorption of pyridine on the pH of the solution was studied to find the optimum pH value. In order to study the effect of pH on the adsorption of pyridine, experiments were carried out at different pHs. The maximum adsorption was found to occur at pH 6.5. Giles isotherm was used and adsorption type was determined.